Invitation to a meeting for the Irish White Cross, Committee for the Maintenance of Orphans from the Secretary, Áine Ceannt - Ceannt, Áine, 1880-1954
Includes the stamp of the ish White Cross (Children's Relief) Association.
Keywords: Ceannt, Áine, -- 1880-1954 -- Correspondence; Irish White Cross (Children's Relief) Association; Charities -- Ireland; Ireland -- History -- 1922-